1992
DOI: 10.1295/polymj.24.871
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sucrose on the Thermo-Reversible Gel-Sol Transition in Agarose and Gelatin

Abstract: The effects of sucrose on the elasticity and thermo reversible gel-sol transition in agarose and gelatin gels were studied. The concentration and temperature dependence of the elastic modulus was analysed by current theories of gel elasticity. The gel-sol transition observed by differential scanning calorimetry was discussed or the basis of a zipper model approach. It was suggested that the number of junction zones increased, the size of each junction zone decreased, and the rotational freedom of a link in a z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 10 publications
3
30
0
Order By: Relevance
“…Their analysis of the shear modulus as a function of gelatin concentration based on an equation derived from the rubber elasticity theory showed that the junction zones of the gelatin gels become smaller but at the same time more numerous by the addition of sucrose [2]. Nishinari et al applied a zipper model approach to the analysis of differential scanning calorimetry (DSC) data for gelatin gels containing sucrose and the obtained results are consistent with those of Oakenfull et al [3].…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Their analysis of the shear modulus as a function of gelatin concentration based on an equation derived from the rubber elasticity theory showed that the junction zones of the gelatin gels become smaller but at the same time more numerous by the addition of sucrose [2]. Nishinari et al applied a zipper model approach to the analysis of differential scanning calorimetry (DSC) data for gelatin gels containing sucrose and the obtained results are consistent with those of Oakenfull et al [3].…”
Section: Introductionsupporting
confidence: 53%
“…An aqueous solution of 0.5 M KSCN was used as a solvent [13]. Dilute solutions for SLS measurements were prepared at four concentrations near c = 1.0, 2.0, 3.0 and 4.0 × 10 -3 g/cm 3 . SLS measurements were carried out over the angular range of 30° to 135° at intervals of 15° with vertically polarized incident light at 632.8 nm of He-Ne laser.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugars dissolve in water and restructure by hydration shells the water molecules locally, rather than using the models as discussed by [69]. Thus water is not an inert background of good solvent, which manifests itself by the change of the gelling properties when different sugars are added.…”
Section: Influence Of Sugars and Other Low Molecular Co-solventsmentioning
confidence: 99%
“…Solutions of some biopolymers such as methyl cellulose [7] , xyloglucan from which galactose residues are removed [8] , curdlan [9−10] , glycinin and β-conglycinin [11−12] form a gel on heating, while solutions of other biopolymers such as agarose [13] , carrageenan [14] , gelatin [13,15] and gellan [16−17] form a gel on cooling. The gelation mechanism of heat-set gels has been recently reviewed [18] .…”
Section: Introductionmentioning
confidence: 99%